IDENTIFIKASI TIPOLOGI BIOGENETIK PROTEIN DARAH IKAN NILA DI PASAR TRADISIONAL KOTA MATARAM PROVINSI NUSA TENGGARA BARAT - Nofisulastri Nofisulastri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2013)
Sampling (parrot fish) is randomized sampling, ie traditional market (Kebon Roek Ampenan, East Sukaraja Ampenan, and Pagesangan) in Mataram City of West Nusa Tenggara Province. Research method based on standard morphometric measurement and electrophoresis analysis of SDS-PAGE. Fifteen characters measured from six fish samples representing the sampling sites showed that morphologically allegedly there were two different groups of parrot fish samples with striking differences found in the color patterns below the jaws and the color patterns of the fins. Based on the analysis of SDS-PAGE, it is assumed that there are 3 (three) biogenetic diversity seen from the existence of the amount of blood protein band based on 5 standard protein locus, that is 8 protein band (2 sample of parrot fish) and 9 protein band for 4 sample of other parrot fish two different types of allele locations).